If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -14 + 3x = x Solving -14 + 3x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -14 + 3x + -1x = x + -1x Combine like terms: 3x + -1x = 2x -14 + 2x = x + -1x Combine like terms: x + -1x = 0 -14 + 2x = 0 Add '14' to each side of the equation. -14 + 14 + 2x = 0 + 14 Combine like terms: -14 + 14 = 0 0 + 2x = 0 + 14 2x = 0 + 14 Combine like terms: 0 + 14 = 14 2x = 14 Divide each side by '2'. x = 7 Simplifying x = 7
| 6a+7b=19 | | 3x-10=2x+20 | | 5(1a-4)=44 | | 4s=5s+6 | | 3(x-2)=2x+3+x | | X^2-25x+256=0 | | 18=2[x+6] | | 10p=6+7p | | 5x+50=-95 | | g+10=-9g | | a=15-b | | 8n-10=10n+10 | | x=-27+-2.25y | | ab=56 | | 3x-4+2y= | | 2(a-2)=49(2a-4) | | (2x+6)+(2x+5)+(2x)=(2x)+(2x)+(3x+2) | | -3q-8=10-5q | | -8z+8=-7z | | 1t^2-300t+45000= | | 8g+41=6g+95 | | 3(y+4)+2=29 | | 1.8+2.5= | | 4s-10=6s | | 4(5x+2)=Y | | 10-3u=-5u-4 | | 4(x-1)+2x=6(x-6) | | 4s+7t=79 | | -8g=-9g+3 | | p=-5+2p | | 2(5)+3(0)= | | 6x+2x+x+3=39 |